Impact of Discovery Learning with Reflective Learning Journals on Students' Critical Thinking in Environmental Change Topic - Chusnunnia Chusnunnia; Joko Ariyanto; Kistantia Elok Mumpuni (Bioedukasi: Jurnal Pendidikan Biologi, 2025)
One of the issues in biology education is the low level of students’ critical thinking skills. This is primarily due to conventional, teacher-centered learning approaches that do not allow students to develop their thinking. Therefore, innovative teaching strategies are needed to enhance students’ critical thinking abilities, like the discovery learning model integrated with reflective learning journals. This study aims to investigate the impact of the discovery learning model integrated with reflective learning journals in improving students’ critical thinking skills, including an analysis based on high and low academic abilities. This quasi-experimental study employs a pretest-posttest control group design. The sample was selected using cluster random sampling at SMA Negeri 2 Karanganyar, with class X-E8 as the control group and class X-E6 as the experimental group. Primary data was collected with observation sheets, tests, and documentation. Hypothesis testing was conducted using ANCOVA and N-Gain tests. The findings indicate significant differences in students’ critical thinking skills on environmental changes when taught using the discovery learning model alone compared to the discovery learning model combined with reflective learning journals. Moreover, differences were observed based on students’ high and low academic abilities. Combining the discovery learning model with reflective learning journals enables students to identify and formulate problems based on observed phenomena, determine learning objectives, gather data, draw conclusions, and articulate their thoughts through reflective journal writing. This instructional approach is used for broader implementation and further investigation to assess its impact on other learning outcomes.